PSYCHOLOGICAL ASPECTS OF PSYCHOEMOTIONAL AND VOLUNTARY PROPERTIES IN FORMING A RESERVE OF MANAGEMENT PERSONNEL - Abdullajanova Dilnozakhon Sultanbekovna (Scholar Express Journals, 2025)
The presence of highly qualified specialists as part of the organization’s human resources allows for a significant reduction in personnel recruitment costs and, as a result, for their adaptation, as well as for creating a system for investing in personnel development. Such investments have a significant impact on staff motivation and help retain staff in the organization, which reduces the level of staff turnover, as well as reduces risks in the event of temporary absence of management personnel and other force majeure situations. The article below provides a comparative analysis of the psychological aspects of psycho-emotional and volitional characteristics in the formation of a reserve of management personnel.
Keywords: Personnel reserve; volitional characteristics; management